Association in a Chinese population of a genetic variation in the early B-cell factor 1 gene with coronary artery disease. Issue 1 (December 2017) - Li, Yafei; Xie, Zhiyong; Chen, Lei; Yan, Jianjun; Ma, Yao; Wang, Liansheng; Chen, Zhong
Abstract Background Early B-cell factor 1 (EBF1) is a transcription factor expressed primarily during early B cell development. Previous studies have shown EBF1 regulates blood glucose and lipid metabolism in mice with diabetes and central adiposity. Recently, a genetic variation (rs36071027) located in an EBF1 gene intron was associated with carotid artery intima-media thickness. However, whether this polymorphism is actually linked with coronary artery disease (CAD) and its severity remains unclear. Methods This study includes 293 CAD cases and 262 controls without CAD. All participants were devided into two groups based on their coronary angiography results. A polymerase chain reaction-ligase detection reaction was used to identify genotypes at rs36071027, and CAD patients were further divided into subgroups with one-, two-, or three-vessel stenosis reflective of CAD severity. Results The frequency of the rs36071027 TT genotype was significantly higher in CAD cases versus controls (4.8% vs. 1.5%, 95% CI: 1.13-10.81P  = 0.029). Subjects with a variant genotype T allele had an increased risk of CAD compared to C allele carriers (additive model: 95% CI: 1.13-2.23, P  = 0.008). After adjustment for cardiovascular risk factors, analysis of the additive and dominant models involving rs36071027 also revealed that T allele carriers had a significantly higher risk for CAD than C allele carriers (additive model: OR 1.56, 95% CI 1.10–2.22, P  = 0.013; dominant model: OR 1.60, 95% CI 1.07–2.41, P  = 0.023). Furthermore, both diabetes and the CT + TT rs36071027 genotype were significantly associated with three-vessel stenosis. Conclusion Our results in a Chinese population suggest that the TT genotype and T alleles in rs36071027 in the EBF1 gene are associated with an increased risk of CAD and its severity.